Aftercare Services for Juvenile Parolees with Mental Disorders in Ohio, 2005-2006 - Stevens, Jack ([Verlag nicht ermittelbar], 2013)
The purpose of the study was to examine the aftercare services juvenile parolees with mental disorders receive as they transition from correctional facilities to the community. The study assessed rates of recidivism for juvenile parolees with mental disorders, the type and frequency of mental health care received in the community by youth on parole, and the relationship between parolees' recidivism and functional outcomes with their utilization of mental health care. The sample came from the Ohio Department of Youth Services (DYS), which covers youths aged 10 to 21 sentenced to correctional care for the 88 Ohio counties in 2005 and 2006. The actual cohort was composed of 175 youths aged 12 to 19 years who had a presumptive release date within the next 60 days and were placed on the mental health caseload. Data were collected in 2005 and 2006 at four time points: one month pre-release, one month post-release, three months post-release, and six months post-release. Variables were gathered from the Ohio DYS and through the administration of a variety of standardized surveys and interview protocols. The main categories of variables include variables relating to arrest history and recidivism, variables relating to the mental health of subjects, variables relating to the administration of mental health treatment and health insurance coverage post-release, and demographic variables.